2019
DOI: 10.1177/2319714519836306
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Empirical Research on Global Talent Management

Abstract: Global talent management as an academic field is regarded as a multi-disciplinary bridge field, which has recently emerged from the strategic international human resource management (HRM) and talent management fields as a critical strategic issue for multinational firms. While some literature reviews have been conducted on the topic, there is no systematic review of drivers, outcomes and challenges in empirical global talent management research. This study therefore provides a rigorous systematic review of emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…The contribution of this paper is in two main folds: first, although some reviews on talent management were conducted, none has paid attention to the specific context of Africa. Specifically, researchers such as Gallardo-Gallardo and Thunnissen (2016) and McDonnell et al (2017) systematically reviewed the talent management generally, Anlesinya et al (2019a), Collings and Mellahi (2009) reviewed strategic talent management scholarship, whereas Anlesinya et al (2019b) and Tarique and Schuler (2012) provided a review on empirical and conceptual domains of global talent management research respectively. However, none has focused on talent management outcomes and challenges as well the nature of research method in talent management research in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…The contribution of this paper is in two main folds: first, although some reviews on talent management were conducted, none has paid attention to the specific context of Africa. Specifically, researchers such as Gallardo-Gallardo and Thunnissen (2016) and McDonnell et al (2017) systematically reviewed the talent management generally, Anlesinya et al (2019a), Collings and Mellahi (2009) reviewed strategic talent management scholarship, whereas Anlesinya et al (2019b) and Tarique and Schuler (2012) provided a review on empirical and conceptual domains of global talent management research respectively. However, none has focused on talent management outcomes and challenges as well the nature of research method in talent management research in Africa.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, in the review of global research on whistleblowing, it was found that the majority of studies have the US institutional context, whereas research on Indian context is almost negligible. However, ample studies are conducted to review the literature and methodological trends and patterns in a various subject matters, that is, corporate governance, talent management, and international marketing literature (Anlesinya, Dartey-Baah, & Amponsah-Tawiah, 2019; Rana & Sharma, 2016; Srinivasan & Srinivasan, 2011). For example, a study was conducted by Rana and Sharma (2016), where the authors attempted to develop a broad conceptual framework for the international marketing research process and also categorized methodologies, conducted as a rigorous systematic review based on an assessment of articles on international marketing published in academic journals between 1990 and 2012.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Moreover, recent systematic reviews reveal that multilevel research in the TM field is limited (Anlesinya et al , 2019c). We, therefore, responded to Anlesinya et al ’s (2019c) recent call for multilevel TM research and further extends Thunnissen et al ’s (2013) work on the multilevel and multi-value of TM by arguing that RTM improves perceived decent work, employee well-being and organisational well-being directly.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent systematic reviews reveal that multilevel research in the TM field is limited (Anlesinya et al , 2019c). We, therefore, responded to Anlesinya et al ’s (2019c) recent call for multilevel TM research and further extends Thunnissen et al ’s (2013) work on the multilevel and multi-value of TM by arguing that RTM improves perceived decent work, employee well-being and organisational well-being directly. Furthermore, employee perception of decent work and employee well-being serve as mechanisms through which RTM leads to improvement in organisational well-being in terms of strong financial performance and competitiveness; attractive reputation and social legitimacy; talent retention; and learning and innovation.…”
Section: Introductionmentioning
confidence: 99%